Effects of dietary N-carbamylglutamate supplementation on growth performance, tissue development and blood parameters of yellow-feather broilers. (22nd January 2019) - Hu, Yan; Shao, Dan; Wang, Qiang; Xiao, Yunqi; Zhao, Xu; Shen, Yiru; Zhang, Shan; Tong, Haibing; Shi, Shourong
ABSTRACT: The effects of N-carbamylglutamate (NCG ) on the growth performance, tissue development, and blood parameters of broilers are unknown. In this study, 2 linked experiments were conducted to investigate the effects of 4 graded dietary levels and 3 dietary stages of NCG in a Chinese indigenous yellow-feather broiler breed during 2 growth phases: 1 to 18 d and 19 to 36 d. The dietary levels of NCG were 0.05%, 0.10%, 0.15%, and 0.20%, and dietary stages were designed to add NCG during the starter stage or grower stage or throughout the experimental period. At the age of 18 d, graded doses of NCG from 0.05 to 0.20% in the diet produced quadratic ( P < 0.05) positive responses in body weight, width of intermuscular fat cingulum, liver weight, serum blood urea nitrogen, and serum low-density lipoprotein as well as linear ( P < 0.05) positive responses in albumin serum concentration. The average feed per gain and mortality were unaffected by dietary NCG levels. Among 3 dietary treatments, only NCG dietary treatments throughout the experimental period improved the body weight and daily weight gain linearly ( P < 0.05). The daily weight gain under the 3 dietary treatments used indicated that the most fitting dose is 0.1% NCG among the 4 dietary levels of NCG ( P < 0.05). At this dose, muscle weight increased, whereas subcutaneous adipose as well as the serum contents of uric acid, triglyceride, and albumin decreased. Considering the growth performance and tissue development under the conditions used in this study, the best-fit model for NCG requirements of Chinese yellow-feather broilers was estimated from regression analysis to be 0.09 to 0.12% dietary NCG treatments during the grower stage. The modified blood parameters indicated that NCG dietary effects on broiler growth may be accompanied by modified homeostasis of arginine metabolism, lipid deposition, protein synthesis, and immune response.